If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -23 = -23 + 6t Reorder the terms: -23 + 5t = -23 + 6t Add '23' to each side of the equation. -23 + 23 + 5t = -23 + 23 + 6t Combine like terms: -23 + 23 = 0 0 + 5t = -23 + 23 + 6t 5t = -23 + 23 + 6t Combine like terms: -23 + 23 = 0 5t = 0 + 6t 5t = 6t Solving 5t = 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 5t + -6t = 6t + -6t Combine like terms: 5t + -6t = -1t -1t = 6t + -6t Combine like terms: 6t + -6t = 0 -1t = 0 Divide each side by '-1'. t = 0 Simplifying t = 0
| y-60=7493 | | (6n-10)/(n-4) | | 14-x=2+5 | | 0.4x-2=0.6x | | 0.4y+2x=1.2 | | 18x^2+5x-72=0 | | X+18=296 | | 6x-4y-3x+4=0 | | 5n-28=-64+9n | | 27=90c | | 140=-10n | | 6y+7=4y-3 | | S=12-a/4 | | -6x+20=-4x-22 | | 4/3=r-8/9 | | Y+20=5y-8 | | 0.25+9=-12 | | 9x-6=3(-4+3x)+6 | | (x+4)+(4y-8)=180 | | 0.25+9=-13 | | 12x-24=4x-32 | | 28v-21= | | 9x-5=9(x+2)-11 | | 4y+2=-3y+19 | | g(f(-2))= | | 3.75w=35 | | 5x-3=12x-30 | | (4cotx-1)(sinx+1)=0 | | 27=9t-9 | | 2x+4-4x=-2(X-2) | | 5n+6=10n+3 | | 2(3+5x)-5=4 |